2015
DOI: 10.1097/id.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium From Mesenchymal Stem Cells Enhances Early Bone Regeneration After Maxillary Sinus Floor Elevation in Rabbits

Abstract: MSC-CM is a promising novel therapeutic agent to promote bone regeneration after maxillary sinus floor elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…A PLGA membrane with incorporated MSC‐CM promoted modest, but significantly higher bone formation compared to biomaterial controls in rat calvaria defects [ 220 ] and β‐TCP soaked with MSC‐CM led to earlier angiogenesis and bone regeneration in a sinus floor elevation rabbit model, but no overall increase in bone formation at 8 weeks. [ 221 ] Recent research which employed EVs isolated from MSC‐CM suggests therapeutic potential of EV‐functionalized biomaterials for bone repair. EV‐loaded β‐TCP scaffolds promoted bone regeneration in critical‐sized rat calvaria defects in a dose‐dependent manner, with EV‐mediated osteogenic differentiation mediated through activation of the PI3K/Akt signaling pathway.…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…A PLGA membrane with incorporated MSC‐CM promoted modest, but significantly higher bone formation compared to biomaterial controls in rat calvaria defects [ 220 ] and β‐TCP soaked with MSC‐CM led to earlier angiogenesis and bone regeneration in a sinus floor elevation rabbit model, but no overall increase in bone formation at 8 weeks. [ 221 ] Recent research which employed EVs isolated from MSC‐CM suggests therapeutic potential of EV‐functionalized biomaterials for bone repair. EV‐loaded β‐TCP scaffolds promoted bone regeneration in critical‐sized rat calvaria defects in a dose‐dependent manner, with EV‐mediated osteogenic differentiation mediated through activation of the PI3K/Akt signaling pathway.…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…The therapeutic effects of mesenchymal stem cell‐conditioned media have been explored in other diseases, such as ischemic heart disease, brain injury, spinal cord injury and bone defects. The use of cell‐free therapies, such as conditioned media from mesenchymal stem cells, has specific advantages over stem cell‐based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that MSC-CM contains cytokines such as IGF-1, VEGF, and TGF-β1, which may synergistically affect migration, angiogenesis, and osteogenic differentiation of host MSCs [5, 6, 9, 10]. The effects of these three cytokines are thought to be very complex, although IGF-1 is believed to regulate the migration of osteoblasts [20] and MSCs [21], and sustained systemic or local infusion of IGF-1 was shown to enhance bone formation [22], while TGF-β1 stimulates migration of osteoprogenitor cells and regulates cellular proliferation, differentiation, and production of extracellular matrix [23].…”
Section: Discussionmentioning
confidence: 99%
“…These secretomes will be released from the implanted cells and will establish a new blood supply via migration of endothelial cells to the sites of bone defects and subsequent angiogenesis. Our previous study reported that MSC-CM enhanced the migration of MSCs, tube formation of human umbilical vein endothelial cells (HUVECs), expression of osteogenic and angiogenic markers of MSCs in vitro, and bone and periodontal regeneration in vivo [810]. We hypothesized that angiogenesis is an important step for bone regeneration and that VEGF is a crucial factor in MSC-CM that enhances its osteogenic potential.…”
Section: Introductionmentioning
confidence: 99%